Chromosomal Microarray Analysis Results From Pregnancies With Various Ultrasonographic Anomalies. Issue 6 (December 2018) - Sagi-Dain, Lena; Maya, Idit; Reches, Adi; Frumkin, Ayala; Grinshpun-Cohen, Julia; Segel, Reeval; Manor, Esther; Khayat, Morad; Tenne, Tamar; Banne, Ehud; Shalata, Adel; Yonath, Hagith; et al.
Abstract : OBJECTIVE: To examine chromosomal microarray analysis results in pregnancies with various ultrasonographic anomalies and to characterize the copy number variants in diverse fetal phenotypes. METHODS: We retrospectively examined chromosomal microarray analyses of amniocenteses performed nationwide as a result of fetal ultrasonographic anomalies (structural defects, fetal growth restriction, and polyhydramnios) between January 2013 and September 2017. The rate of abnormal chromosomal microarray findings was compared between the different phenotypes and with a previously described control population of 15, 225 pregnancies with normal ultrasonographic findings. RESULTS: Clinically significant chromosomal microarray aberrations were detected in 272 of 5, 750 pregnancies (4.7%): 115 (2%) karyotype-detectable and 157 (2.7%) submicroscopic. Most commonly detected copy number variants were 22q11.21 deletions (0.4%) followed by 22q11.21 gain of copy number (0.2%). Specific copy number variants detected among pregnancies with abnormal ultrasonographic findings were up to 20-fold more prevalent compared with low-risk pregnancies. Some variants were associated with specific phenotypes (eg, 22q11.21 microdeletions with cardiovascular and 17q12 microdeletions with genitourinary defects). CONCLUSION: The rate of abnormal amniotic chromosomal microarray analysis results is twice that of karyotypic abnormalities in pregnancies with various abnormal ultrasonographic findings. Abstract : The rate of abnormal amniotic chromosomal microarray analysis results in pregnancies with various abnormal ultrasonographic findings is twice that of karyotype-detectable abnormalities.